POLA KONSUMSI MAKANAN OLAHAN DAN KEJADIAN HIPERTENSI DI RUMAH SAKIT UMUM DAERAH PRABUMULIH TAHUN 2012 - Susyani, Susyani; Rotua, Manuntun; Suryani, Ema (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2013)
The increased prevalence of cardiovascular disease each year become a major problem in developing and developed countries. Based on data from the Global Burden of Disease (GBD) in 2000, 50% of cardiovascular disease caused by hypertension. Diet and lifestyle that consume processed foods high in fat and low in fiber can lead to and increase the risk of hypertension. Thepurpose of this study to determine the relationship of eating processed foods with incidence of hypertension in the General Hospital Prabumulih 2012. This study is an analytic survey with crosssectional research design. The population in this study were all patients who seek treatment at an outpatient poly General Hospital Prabumulih in October 2011 were diagnosed with hypertension or not. Sampling technique in this study is accidental sampling. The determination of the samples using the formula (Lemeshow, 2002) the importance of the total sample of 89 people. Chi-Square Test results indicate that there is a correlation between age (p value 0.003), and a diet of processed foods (p value 0.007) and the incidence of hypertension. The type of materials processed foods are often consumed by the respondent is instant noodles, canned sardines, smoked fish, boiled fish, Rosep, shredded, salted eggs, salted fish, sausages, while fatty foods are often consumed tunjang. There isno relationship between sexes with the incidence of hypertension (p value 0.404). It is expected that health practitioners can improve education to increased public knowledge about healthy diet and hypertension, and motivate people to live healthier.